Quantum wave packet study of the insertion reaction S+H2 - Bulut, N; Gogtas, F; Akpinar, S (Elsevier, 2004)
S(D-1)+H-2-->SH+H reaction at zero total angular momentum has been studied by using a time-dependent quantum real wave packet method. State-to-state and state-to-all reactive scattering probabilities for a broad range of energy are calculated. The probabilities show many sharp peaks that ascribed to reactive scattering resonances. The density plots of the wave function shows that the reaction presents a pure insertion pathway. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: reactive scattering; insertion reaction; wavepacket study